1993
DOI: 10.1111/j.1526-4610.1993.hed3308436.x
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy in a Headache Centre Population

Abstract: In this paper we report the prevalence of self-medication and polypharmacy in our patient population at the John R. Graham Headache Centre at the Faulkner Hospital, Boston. One hundred fifty patients were interviewed when they called the Headache Centre and spoke to a triage nurse. A significantly higher number of women than men called in for triage counselling. Sixty-nine percent of the patients reported taking non-Headache Centre medications, either prescribed or over the counter (OTC); 39% of the patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
0
7
0
Order By: Relevance
“…Polypharmacy is common in a Headache Centre population. 14 In the case of CM group (Fig. 4), where 73% of the patients were daily taking nonheadache drugs, above all sedativehypnotics (30%), followed by antihypertensive agents (26%) and antidepressants (23%), polypharmacy was probably a consequence of their comorbid diseases and the result of their frequent and different consultations.…”
Section: Commentsmentioning
confidence: 97%
See 1 more Smart Citation
“…Polypharmacy is common in a Headache Centre population. 14 In the case of CM group (Fig. 4), where 73% of the patients were daily taking nonheadache drugs, above all sedativehypnotics (30%), followed by antihypertensive agents (26%) and antidepressants (23%), polypharmacy was probably a consequence of their comorbid diseases and the result of their frequent and different consultations.…”
Section: Commentsmentioning
confidence: 97%
“…3) suffered above all from psychiatric disorders (67%) (anxiety and depression), followed by gastrointestinal disorders (43%), perhaps due to the overuse of NSAIDs, alone or combined. Polypharmacy is common in a Headache Centre population 14 . In the case of CM group (Fig.…”
Section: Commentsmentioning
confidence: 99%
“…A clinic‐based study by Oates et al found that 69% of headache patients were on one or more medication that was not intended for headache prevention 15 . Many of these non‐headache prescriptions were substances that impacted preventative therapy such as hormones, antidepressants, and antihistamines.…”
Section: When To Consider Combination Therapymentioning
confidence: 99%
“…In Heinisch's 4 study, self‐medication was reported by 89.9% of those interviewed, while the medication was prescribed by a physician in only 8.8% of the cases. Oates et al 17 found that 69% of the patients treated at the Graham Headache Center of the Faulkner Hospital in Boston used medications not prescribed to them. Amayo et al 3 concluded from the results of their research that the main reason for not consulting a doctor for headache was self‐medication; this occurred in 56% of the students with headaches.…”
Section: Commentsmentioning
confidence: 99%